Dehydrated cashew apple in different grinding sizes to sheep - Araújo, Alexandre Ribeiro; Costa, Joaquim Bezerra; Rogério, Marcos Cláudio Pinheiro; Carneiro, Maria do Socorro de Souza; Muniz, Luciano Cavalcante; Fontenele, Rildson Melo; Silva, Vandenberg Lira (Acta Scientiarum. Animal Sciences, 2022)
The cashew pseudo fruit can be used to animal feeding in tropical and subtropical countries as Brazil, Ivory Coast and Vietnam. Thus, our objective was to evaluate the intake, digestibility of nutrients and nitrogen balance of dehydrated cashew apple by-product to sheep. The experiment was carried out with 24 sheep in a completely randomized design with the treatments distributed in a 4 x 2 factorial scheme to test the inclusion (11, 21, 28 and 33% dry matter basis) and the grinding sizes (3 and 19 mm diameter) of dehydrated cashew apple by-product. To grinding sizes there was no effect to intake and digestibility, suggesting the use of dehydrated cashew apple by-product either finely or coarsely milled. The inclusion up to 33% of dehydrated cashew apple by-product inclusion did not affect voluntary intake and nitrogen balance. However, when including above 21%, there was a reduction of ether extract digestibility and more than 28% reduced dry matter and organic matter digestibility.